Evaluation of fungal and bacterial antagonists' seed treatment for controlling damping-off disease in forest nurseries - Arya, Sanjay; Kaushik, J. C. (Universiti Putra Malaysia Press, 2003)
Biological control potential of six well reported biocontrol agents, Trichomerma viride, T. harzianum, Gliocladium virens, Bacillus sp., B. subtilis and Pseudomonas fluorescens against Rhizoctonia solani, R. bataticola, Fusarium oxysporum, F. moniliformae, F. solani and Phythium aphanidermatum causing damping-off in forest nurseries was studied in vitro and under screen house conditions. In vitro evaluation of biocontrol agents by dual inoculation method revealed that P. fluorescens, Bacillus sp. and T. viride significantly inhibited mycelial growth of the damping-offfungi. In pot experiments, seed treatment of T. viride and P. fluorescens proved superior to other fungal and bacterial biocontrol agents in reducing damping off (pre and post emergence) incidence compared to untreated controls.